Rearrangements of organic peroxides and related processes - Yaremenko, Ivan A; Vil’, Vera A; Demchuk, Dmitry V; Terent’ev, Alexander O (Beilstein journal of organic chemistry, 2016)
This review is the first to collate and summarize main data on named and unnamed rearrangement reactions of peroxides. It should be noted, that in the chemistry of peroxides two types of processes are considered under the term rearrangements. These are conventional rearrangements occurring with the retention of the molecular weight and transformations of one of the peroxide moieties after O–O-bond cleavage. Detailed information about the Baeyer−Villiger, Criegee, Hock, Kornblum−DeLaMare, Dakin, Elbs, Schenck, Smith, Wieland, and Story reactions is given. Unnamed rearrangements of organic peroxides and related processes are also analyzed. The rearrangements and related processes of important natural and synthetic peroxides are discussed separately.